Intestinal permeability in children with Crohn's disease and coeliac disease. Issue 6334 (3rd July 1982) - Pearson, A D; Eastham, E J; Laker, M F; Craft, A W; Nelson, R
Abstract : Mannitol and lactulose were used as probe molecules to measure intestinal permeability in children with active small-bowel Crohn's disease and with untreated coeliac disease. Mannitol and lactulose were administered by mouth in a moderately hypertonic solution (580 mmol (mosmol)/l), and results were expressed as the ratio of the molecules excreted in urine over five hours. Patients with Crohn's disease had a sixfold increase in permeability (due to increased lactulose permeability) and those with coeliac disease a fivefold increase (due to decreased mannitol permeability). From these results the test offers potential as a noninvasive investigation in children with small-bowel disease.